Job satisfaction among staff nurses in Kuala Lumpur Hospital 1996 - Param Jeeth Singh; Raja Jamaluddin Raja Abd. Majid (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Staff nurses should possess job satisfaction to ensure that quality nursing care is given to the patients. Job satisfaction is important so that productivity does not fall and turnover of personal is not high. Hence, a cross sectional study was carried out among the staff nurses in Kuala Lumpur Hospital to determine the factors influencing job satisfaction and intention to resign. Seven units were chosen by simple random and proportionate sampling was done to get 330 staff nurses. Data was obtained through a self-administered questionnaire. The response rate was 92.4%. Based on ethnicity, 77.4% of the respondents were Malay, 15.4% Chinese and 7.2% Indians. Generally, respondents were dissatisfied with workload and rewards while they were satisfied with interpersonal staff relationships and with status and autonomy. Meanwhile they had neutral attitude towards career development. This study found that 56.4% of staff nurses were generally satisfied while 27.6% were dissatisfied with their jobs and the remainder were neutral. With regards to intention to resign within the next one year. 28.9% of the respondents had no intention to resign at all while 19.3% of respondents had 100% intention to resign from their jobs. Initial analysis found no associations between the social demography factors like ethnicity, age, marital status, duration of service as staff nurses, income and duration of contract as staff nurses with general job satisfaction (p > 0.05). There were associations between the social demography factors as mention above toget11er wit11 general job satisfaction with intention to resign. From the multiple linear regression analysis, predictors of intention to resign were ethnicity, age, duration of service as staff nurses and general job satisfaction. It is hope that the findings of t11jS study will be helpful to the organization of Kuala Lumpur Hospital in addressing the problems of the staff nurses and hence improve the job satisfaction among the staff nurses.